GENERATION Z: CONSUMER BEHAVIOR IN DIGITAL ECOSYSTEM - T. A. Beregovskaya; S. A. Grishaeva (Вестник университета, 2020)
The behavioral matters of Generation Z, who use the possibilities of the Internet to meet their needs, have been considered. There is no universal digital format. The company’s interaction with the consumer facilitates the implementation of an omnichannel marketing strategy that creates conditions for their continuous interaction, as easy and convenient as possible to meet existing expectations, requests, and needs. As a result of the study, the opportunities (consumer’s independent choice of means of interaction with the manufacturer, channel shifting in the process of purchasing, interaction with the manufacturer regardless from the chosen communication channel) and barriers (absence of isolated online channels for sales, usage of slow-loading Internet platforms with inconvenient interfaces, absence of a dedicated app or limited possibilities of its usage, etc.) of omnichannel marketing implementation for the Generation Z target audience have been revealed. Their media preferences, such social networks as VKontakte, Instagram, YouTube, Facebook, were defined. It has been determined, that Generation Z’s consumer expectations and consumer behavior are influenced by opinion leaders and reference groups, these mainly being bloggers, peers and occasionally older companions, whom they find in social networks.